Recycling and reuse of used tyres proceedings of the international symposium organised by the Concrete Technology Unit, University of Dundee and held at the University of Dundee, Scotland on 19-20 March 2001 - Dhir, Ravindra K.; Limbachiya, Mukesh C.; Paine, Kevin A. (Thomas Telford, 2001)
Substantial quantities of used tyres are being discarded annually throughout the world and this is likely to increase in line with the growth in road traffic. Given the environmental economic implications of this waste, the many regulating bodies world-wide are actively promoting policies aimed at recycling and reuse of the material for recovery as a valuable resource. However, in many parts of the world, recycled tyre technology is still in its infancy. This book presents the proceedings of an International Symposium organised by the Concrete Technology Unit, University of Dundee which brings together some of the world's leading experts in the field of used tyre recycling.